Parasitoides de Periplaneta americana (Linnaeus, 1758) (Blattaria: Blattidae) em zona urbana de Manaus, Amazonas, Brasil - Lima, Adriane G. M.; Nascimento, Alexsandra C.; Fernandes, Daniell R. R. (Entomological Communications, 2022)
In Brazil, synanthropic cockroaches are considered one of the insect groups of greatest economic importance. Aprostocetus hagenowii (Ratzeburg, 1852) (Hymenoptera: Eulophidae) and Evania appendigaster (Linnaeus, 1758) (Hymenoptera: Evaniidae) are parasitoid species that are natural enemies of Periplaneta americana (Linnaeus, 1758) (Blattaria: Blattidae) and can be adopted in biological control. Here we point out the occurrence of A. hagenowii parasitizing P. americana oothecae as the first record of this species for the northern region of Brazil, in the Amazonas State. Furthermore, we highlight the synanthropic distribution of E. appendigaster, based on specimens deposited in the Coleção de Invertebrados do Instituto Nacional de Pesquisas da Amazônia (INPA), Brazil.